Infective Endocarditis Caused by Abiotrophia defectiva: A Unique Case Complicated by Mitral Valve Perforation - Ra'ed Ababneh (20905286) (2025)
Abiotrophia defectiva, a nutritionally variant streptococcus, represents a rare yet serious cause of infective endocarditis (IE), accounting for 1%–2% of the total IE cases. It affects native valves in 10% of patients, and it is implicated in catastrophic complications. A 33‐year‐old medically free male presented with a persistent nonproductive cough for 4 months. It was associated with unintentional weight loss (10 kg); however, he denied any other symptoms. His symptoms started after he had a dental implant. Physical examination was unremarkable except for a systolic murmur. Upon further investigations, a blood culture showed Abiotrophia defectiva, and echocardiography demonstrated severe mitral regurgitation originating from the perforation site located on the posterior leaflet measuring 10 × 4 mm, in addition to 2 masses suggestive of vegetations, the largest measuring 10 × 6 mm. The patient was hospitalized as a case of IE and acute mitral valve regurgitation. In light of mitral valve perforation, large vegetation, and bacteremia, an urgent multidisciplinary decision to proceed with mitral valve replacement was made, and the patient received a total of 6 weeks of antibiotics. Physicians should remain highly vigilant for IE, its rare causes, and associated complications. In addition, managing complex cases of IE necessitates a multidisciplinary team approach between cardiology, infectious diseases, and cardiac surgery teams. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1002/ccr3.70400